Design and optimization of micro-perforated ultralight sandwich structure with N-type hybrid core for broadband sound absorption. (January 2023) - Jiang, Yongfeng; Shen, Cheng; Meng, Han; He, Wei; Lu, Tianjian
Highlights: Micro-perforated sandwich panel with NH core exhibits good sound absorption. Micro-perforated sandwich panel with NH core has multifunctional attributes. Simulated Annealing algorithm is used to optimize micro-perforated sandwich panel with NH core. Abstract: We propose a novel ultralight multifunctional micro-perforated sandwich structure with N-type hybrid core, which exhibits excellent sound absorption as well as good load-bearing capacity and heat transfer performance. Sound absorption coefficient of the sandwich structure is calculated by establishing an analytical model. To validate the analytical model predictions, both experimental measurements and numerical simulations are carried out, with good agreement achieved. Physical mechanisms leading to the excellent acoustic performance of the structure are revealed, and effects of geometric parameters are quantified. For maximized sound absorption at minimal structural weight, an optimization strategy is developed with the Simulated Annealing algorithm. Compared with non-optimal sandwich structures, the optimal structure enables reduced weight and better absorption within broader frequency range. The proposed ultralight sandwich structure with integrated multifunctional attributes has significance in engineering applications demanding excellent mechanical, thermal, acoustic performances as well as low mass and volume.